A Critical Discourse Analysis of Online Youtube News Coverage of South African Discourses on Xenophobia in Democratic South Africa. (1st October 2020) - Asakitikpi, Aretha Oluwakemi; Gadzikwa, Joanah
ABSTRACT: This paper considers news coverage of South Africa as it relates to the continuous occurrence of xenophobia in the country. Through purposely selected news videos uploaded on Youtube, the paper adopts a qualitative content analysis research method guided by the key words 'South African leaders, election speech, xenophobia'. Thirteen videos were purposively selected and transcribed from a list of 18 videos drawn from the first two pages of the keyword search on https://www.youtube.com/results?search_query=South+African+leaders+election+speech+xenophobia . Using Van Dijk's Ideological Square, the qualitative data generated indicate narratives that speak to ideologies binding South Africans together as a 'we' against the migrant 'them'. The binding 'we' factors include the historical Black struggle for liberation, the country's Constitution as well as the Rule of Law. Qualities for 'them' (which the narratives suggest spark xenophobia) include various perceived acts of immigrant criminality; the result of which is economic instability and negative influences on the South African people.